2016
DOI: 10.1017/jfm.2016.716
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment and topology of accelerating shear layers

Abstract: A constantly accelerating circular plate was investigated towards understanding the effect of non-stationarity on shear-layer entrainment and topology. Dye visualizations and time-resolved particle image velocimetry measurements were collected for normalized accelerations spanning three orders of magnitude. Increasing acceleration acts to organize shear-layer topology. Specifically, the Kelvin–Helmholtz instabilities within the shear layer better adhered to a circular path and exhibited consistent and repeatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…With a diameter based Reynolds number superior to 10 4 , the shear layer breaks into small scale vortices (∼ 1 mm) due to a Kevin-Helmholtz instability (Figure 1b). These instabilities have no effect on the accumulation of vorticity in the vortex [15,19].…”
Section: Spatial and Temporal Development Of A Drag Vortex Ringmentioning
confidence: 99%
“…With a diameter based Reynolds number superior to 10 4 , the shear layer breaks into small scale vortices (∼ 1 mm) due to a Kevin-Helmholtz instability (Figure 1b). These instabilities have no effect on the accumulation of vorticity in the vortex [15,19].…”
Section: Spatial and Temporal Development Of A Drag Vortex Ringmentioning
confidence: 99%
“…The life of vortices around bluff bodies often begins with a shear layer (Jeon & Gharib 2004;Fernando & Rival 2016;Fernando et al 2017;Rosi & Rival 2017;Corkery, Babinsky & Graham 2019). When a bluff body moves relative to a fluid flow, a thin layer of fluid emerges at the edge of the body where non-zero shear flow gradients are present.…”
Section: Introductionmentioning
confidence: 99%
“…This range corresponds to a Strouhal number around 0.2, according to the plate geometry and kinematics used by the authors. The secondary vortex shedding frequency behind a vertical flat plate increases with increasing acceleration of the flat plate according to Rosi & Rival (2017). It is crucial to define a scaling parameter, such as the Strouhal frequency for the cylinder case, that allows for a more universal relationship between the shedding frequency or formation time of primary and secondary vortices as a function of the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus about the exponent value of the proposed relationship. Prasad and Williamson (1997) indicated that an exponent value of 0.67 works for Re up to 10 5 and Wei and Smith (1986) (Rosi and Rival, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Every kind of two-dimensional motions can be decomposed into a pure rotation and a translation. An extensive body of literature can be found that discusses the vortex formation behind translating objects (de Guyon and Fernando and Rival, 2016;Rosi and Rival, 2017;Paraz et al, 2016). The vortex formation process on a rotation object has received less attention.…”
Section: Introductionmentioning
confidence: 99%